Salmonella Typhimurium gastroenteritis leading to chronic prosthetic vascular graft infection. (8th August 2017) - Cullinan, Milo; Clarke, Michael; Dallman, Tim; Peart, Steven; Wilson, Deborah; Weiand, Daniel
Abstract : Introduction. It is estimated up to 6 % of prosthetic vascular grafts become infected. Staphylococcus aureus is predominant in early infection and coagulase-negative staphylococci are predominant in late infections. Enterobacteriaceae cause 14–40 % of prosthetic vascular graft infections. This is, to our knowledge the first reported case of Salmonella gastroenteritis causing chronic prosthetic vascular graft infection (PVGI). Case presentation. A 57 years old lady presented with signs and symptoms of prosthetic vascular graft infection. Three years earlier, she had undergone a prosthetic axillo-femoral bypass graft for critical limb ischaemia. The infected prosthetic vascular graft was removed and Salmonella Typhimurium was isolated on culture. In the intervening period, Salmonella Typhimurium was isolated from a faecal specimen, collected during an episode of acute gastroenteritis. Whole-genome sequencing (WGS) showed that the respective Salmonella Typhimurium isolates differed by only a single nucleotide polymorphism (SNP). Salmonella Typhimurium was not isolated on culture of a faecal specimen collected five days following cessation of antimicrobial therapy. Six months after removal of the prosthetic graft, the patient remains under follow-up for her peripheral vascular disease, which currently requires no further surgical intervention. Conclusion. This case has clear implications for the management of chronic PVGI. It is vital to collect high-quality surgical specimens for microbiological analysis and empirical choices of antibiotics are unlikely to cover all potential pathogens. It may also be prudent to enquire about a history of acute gastroenteritis when assessing patients presenting with chronic PVGI.